Better Bioactivity, Cerebral Metabolism and Pharmacokinetics of Natural Medicine and Its Advanced Version - Xie, Jiaxi; Zhong, Cailing; Wang, Tingting; He, Dan; Lu, Luyang; Yang, Jie; Yuan, Ziyi; Zhang, Jingqing (Frontiers in Pharmacology, 2022)
Currently, many people are afflicted by cerebral diseases that cause dysfunction in the brain and perturb normal daily life of people. Cerebral diseases are greatly affected by cerebral metabolism, including the anabolism and catabolism of neurotransmitters, hormones, neurotrophic molecules and other brain-specific chemicals. Natural medicines (NMs) have the advantages of low cost and low toxicity. NMs are potential treatments for cerebral diseases due to their ability to regulate cerebral metabolism. However, most NMs have low bioavailability due to their low solubility/permeability. The study is to summarize the better bioactivity, cerebral metabolism and pharmacokinetics of NMs and its advanced version. This study sums up research articles on the NMs to treat brain diseases. NMs affect cerebral metabolism and the related mechanisms are revealed. Nanotechnologies are applied to deliver NMs (exosomes, nanoparticles, liposomes, lipid polymer hybrid nanoparticles, nanoemulsions, protein conjugation and nanosuspensions) which improve their pharmacological activity and pharmacokinetic behaviors. The structure-based metabolic reactions and enzyme-modulated catalytic reactions related to advanced versions of NMs are presented. Appropriate delivery systems, such as novel nanosystems including exosomes, nanoparticles, LPHNPs, nanoemulsions, protein conjugation and nanosuspensions, provide better pharmacological and pharmacokinetic characteristics for NMs. The structure-based metabolic reactions of NMs alter the pharmacological activities of NMCs.